MESH DEPENDENCY STUDY ON TUNNEL MODELING - Noufal S, Ahmad
In designing a tunnel a software is needed which can analyze the stability of soil and rock masses where the tunnel will be open so the mining activities can run safely. One of the thing that should be considered is plastic zone radius of tunnel. The software that will be used in conducting the modeling is FLAC 8.0. Different mesh size were applied with Mohr-Coulomb and strain-softening behaviour and also different critical plastic strain were applied for strain-softening criterion. Next the shape and value of plastic zone radius of the modeling will be obtained based on two characteristic approaches. Based on the modeling performed the plastic zone radius obtained with Mohr-Coulomb criterion are between 1.5 m to 2.25 m and for the strain-softening criterion are between 1.8 m to 7.25 m. There are significant different values of plastic zone radius with strain-softening criterion. This is caused by differences in mesh and value of critical plastic strain. For Mohr-Coulomb criterion if the mesh size is getting smaller, then the plastic zone radius is also getting smaller. As for the strain-softening criterion if the mesh and critical plastic strain values are getting smaller, then the plastic zone radius will be even greater.